REGISTER PEMANDUAN WISATA PROGRAM CITY TOUR: PENGGUNAAN KOSA KATA, FRASE DAN PERCAKAPAN BAHASA PRANCIS BIDANG PROFESI PARIWISATA - Muhammad Hasyim; Prasuri Kuswarini; Masdiana (JURNAL ILMU BUDAYA, 2021)
Tour guides are guidelines used by guides in providing services to tourists. This paper aims to discuss the register of city tour scouting programs, the use of French vocabulary, phrases and conversation in the tourism profession. The method used in this paper is a case study through tourism scouting training activities by tourism stakeholders. The source of the research data is the text of online tourism promotion media and examples of the results of the city tour program preparation exercise. The conclusion of this paper shows that tour guide is a professional field of tourism that has its register of French that must be understood and mastered by tour guides. With the use of a tour guide register, communication between guides and French tourists can be well established.